PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN PENERAPAN GREEN HOTEL MANAGEMENT TERHADAP KINERJA LINGKUNGAN DI THE DHARMAWANGSA HOTEL JAKARTA DENGAN METODE STRUCTURAL EQUATION MODELLING - Imam Ardiansyah; Irene Amalia Chandra (Sekolah Tinggi Pariwisata Mataram, 2021)
This research is a research that discusses quantitatively to determine the effect on each variable of participatory leadership style and the application of green hotel management on environmental performance by using the Structural Equation Modeling analysis tool with the help of AMOS 2.0 software. The number of representative samples are employees who have worked for two years because these employees already understand how to implement Green Hotel Management at The Dharmawangsa Hotel with a total of 128 employees. In the study there were measurements carried out are validity tests, reliability tests, normality tests and multivarite ouliers tests, Goodness of fit analysis and SEM analysis hypothesis testing. The results showed that for H1 the critical ratio value was 2.526 > 1.96 and the probability value was p = 0.00 < 0.05 this indicates H1 is accepted. For H2 the critical ratio is 3.103 > 1.96 and the probability value is p = 0.00 < 0.05. This shows H2 is accepted. For H3 see the goodness of fit measurement if the model results have met the requirements because the GOF index value has been fulfilled, then for H3 it is accepted. Finding on this research the leader has a key role in integrating the concept of sustainability into the hotel's business goals and strategies in providing examples of duties and authority to make the green hotel program a success in order to improve environmental performance